Spider-Man. Homecoming [videorecording (Blu-Ray + DVD)] - Lee, Stan, 1922-2018; Ditko, Steve (Sony Pictures Home Entertainment, 2017)
Peter Parker balances his life as an ordinary high school student in Queens with his superhero alter-ego Spider-Man, and finds himself on the trail of a new menace prowling the skies of New York City.